Studi Meta Analisis Pengaruh Perilaku Konsumen terhadap Pembayaran Digital - Rizkiyah, Ainun; Windriyati, Windriyati; Qarinah, Uzzatul; Izza, Ahmad Aisa; Nugraha, Budi Sutiono Pratama (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This study aims to analyze the influence of consumer behavior on the adoption of digital payments using meta-analysis methods. Data were collected from six studies involving e-wallet usage in various cities in Indonesia. Trust and ease of use were found to have a significant impact on the adoption of digital payments, with a Fisher's z-transformed correlation coefficient of 0.4381 (95% CI: 0.0796 to 0.7966). Statistical analysis revealed significant heterogeneity among the studies (Q(5) = 102.2233, p < 0.0001, tau² = 0.1912, I² = 95.3110%), indicating variation in the findings. Validity and reliability tests showed that the questionnaire items used were valid and reliable. Publication bias tests through Begg and Mazumdar Rank Correlation, Egger's Regression, and the Trim and Fill method indicated no strong evidence of publication bias. The funnel plot showed a symmetrical distribution, indicating reliable and unbiased results. These findings provide insights for service providers and policymakers to develop effective strategies to enhance digital payment adoption, highlighting the importance of building consumer trust and improving ease of use.